The electrical characteristics of thin film transistors with graphene oxide and organic insulators - Karteri, I.; Karatas, S.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2015)
We have studied the electrical characteristics of nanographene oxide (n-GO) thin film transistor and n-GO organic thin film transistors with poly(methyl methacrylate) (PMMA) and poly-4-vinylphenol (PVP) as organic insulators. One of the alternate methods to prepare GO is achieved by oxidizing graphite via modified Hummers method. In this study, the GO was synthesized by a modified Hummers method. The graphene oxide thin films with PMMA and PVP were prepared by spin coating the precursor solution on a GO/SiO2 dielectrics bilayer. The graphene oxide thin film transistor was found to exhibit a high mobility of 0.375 cm(2)/V.s. This indicates that n-GO film has a more important effect to fabricate a high mobility n-GO thin film transistor than n-GO based thin film transistor with PMMA and PVP. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Graphene oxide; Hummers method; Thin film; Transistor